Designing Educational Games as Learning Media for Lontara/Bugis Script for Children 7-8 Years old: Memory Game with Aksara Lontara Content - Alvanov Mansoor; Ahmad Ade Nugraha (Bina Nusantara University, 2021)
Learning the Bugis tribe local language, especially the introduction of the Lontara script for children, is still being carried out starting from the elementary school level in several areas in South-Sulawesi, including the city of Parepare. This is an effort to preserve one of the traditional scripts that exist in Indonesia while several other traditional scripts have become extinct. There are several problems in implementing lontara script learning: the lack of student mastery of the script, which can be seen from the repetition of teaching materials regarding traditional scripts recognition at several school levels. Educational mobile games have begun to be widely developed as learning media because they can increase children's enthusiasm for learning and smartphone users in Indonesia, including among children. Educational games with the memory game genre can help improve children's mastery of the lontara script. This study uses the Double Diamond method with a formal and dramatic approach to producing an educational game design with lontara script content that can be used as a reference in making script games in South Sulawesi which can be used as learning media for children aged 7-8 years where the material for introducing the characters is taught.